Unified model intercomparison for volcanic ash transport modelling. (1st December 2014) - Morton, Don; Arnold, Dèlia; Webley, Peter; Wotawa, Gerhard; Stunder, Barbara
Our group is pursuing a volcanic ash transport model intercomparison study to evaluate the relative performance of several atmospheric transport models for selected case studies. These intercomparisons require the definition of standard output formats for producing results in a common framework. We define here the common format and develop a set of evaluation tools, allowing for side-by-side comparisons on a level playing field and providing a platform for further quantitative evaluation. The tools developed have widespread applicability to a number of ATM activities and are demonstrated in the realm of volcanic ash transport modelling. The Crater Peak, Mount Spurr eruption of 1992, Alaska, is used as a case study, employing HYSPLIT, FLEXPART and PUFF with common meteorological driving data, and with releases and intrinsic-model set-ups as similar as possible.